LITERATUR DESAIN INSTALASI GAWAT DARURAT (IGD) PADA RUMAH SAKIT DI BEKASI - Sri Prasetya Widodo; Dwi Anggun Riani (SINERGI : Jurnal Riset Ilmiah, 2026)
The Emergency Department (ED) is a healthcare service unit provided by hospitals that delivers rapid, accurate, and integrated initial medical care to patients experiencing critical and/or emergency conditions that threaten life, organ function, or may result in disability, with the objective of preventing death and reducing morbidity and mortality rates. The service system in the ED generally applies a triage system, in which patient care is prioritized based on the level of emergency rather than the order of arrival. Literature on ED design is therefore of significant importance , as it is a requirement stipulated by regulations of the Indonesian Ministry of Health and also plays a crucial role in ensuring a comfortable environment for medical staff and service users, thereby enabling healthcare services to be delivered more effectively and efficiently.